The Integration of Artificial Intelligence (AI) In English Language Teaching Practices: A Meta-Synthesis Study - Rinekso, Aji Budi; Muslim, Ahmad Bukhori; Rodliyah, Rojab Siti (ETERNAL (English Teaching Journal), 2025)
A great number of studies researching the incorporation of AI into English language teaching have grown significantly within the last five years. Nevertheless, to date, limited studies have been found to specifically review studies regarding AI integration in English language teaching. To fill the gap, this meta-synthesis study aims at presenting a summary of qualitative literature exploring how AI is integrated in English language teaching. Sixteen out of forty-seven articles were selected from various reputable databases as well as peer-reviewed journals (i.e., Scopus indexed) including Taylor & Francis, Science Direct, Wiley, Emerald, and ProQuest. Only qualitative data were processed and analysed thematically. Findings revealed some emerging themes: 1) student and teacher’s views towards AI integration in ELT, 2) benefits and drawbacks of AI integration in ELT, and 3) the role of AI for language skill improvement. In addition, the study shed light on several research topics recommended for further research.